The Joint Facial and Invasive Neck Trauma (J-FAINT) Project, Iraq and Afghanistan: 2011-2016. (October 2017) - Lanigan, Alexander; Lindsey, Brentley; Maturo, Stephen; Brennan, Joseph; Laury, Adrienne
Objective: Define the number and type of facial and penetrating neck injuries sustained in combat operations in Iraq and Afghanistan from 2011 to 2016. Compare recent injury trends to prior years of modern conflict. Study Design: Case series with chart review. Setting: Tertiary care hospital. Methods: The Joint Theater Trauma Registry (JTTR) was queried for facial and neck injuries from Iraq and Afghanistan from June 2011 to May 2016. Injury patterns, severity, and patient demographics were analyzed and compared to previously published data from combat operations during January 2003 to May 2011. Results: A total of 5312 discrete facial and neck injuries among 922 service members were identified. There were 3842 soft tissue injuries (72.3%) of the head/neck and 1469 (27.7%) facial fractures. Soft tissue injuries of the face/cheek (31.4%) and neck/larynx/trachea (18.8%) were most common. The most common facial fractures were of the orbit (26.3%) and maxilla/zygoma (25.1%). Injuries per month were highest in 2011 to 2012 and steadily declined through 2016. The percentage of nonbattle injuries trended up over time, ranging from 14.7% to 65%. Concurrent facial/neck soft tissue trauma or fracture was associated with an overall mortality rate of 2.44%. Comparison of our data to that previously published revealed no statistical difference in concurrent mortality (3.5%-2.2%, P = .053); an increase in orbital fractures ( P < .005), facial nerve injury ( P < .0005), and ear/tympanic membrane perforations ( P < .0005); and a decrease in mandible fractures ( P < .005). Conclusion: Penetrating neck and facial injuries remain common in modern warfare. Assessing injury characteristics and trends supports continued improvements in battlefield protection and identifies areas requiring further intervention.